Comparative effectiveness of surgery versus radiotherapy for non-nasopharyngeal head and neck lymphoepithelial carcinoma: An IPTW propensity score analysis - Zhen Zheng; Jiaying Wu; Bing Cao; Yanping Bei; Hui Zhang; Kaitai Liu (PLoS ONE, 2025)
Background Lymphoepithelial carcinoma (LEC) is a rare head and neck malignancy predominately treated with radiotherapy or surgery. However, comparative effectiveness studies, are lacking for non-nasopharyngeal head and neck LEC (HNLEC). Methods Patients diagnosed with non-nasopharyngeal HNLEC from 2000–2019 were extracted from the Surveillance, Epidemiology, and End Results (SEER) database. Inverse probability of treatment weighting (IPTW) was used to balance baseline characteristics. Cancer-specific survival (CSS) was compared between surgery and radiotherapy groups using Kaplan-Meier analyses and Cox regression before and after IPTW adjustment. Results 248 patients were included. Before IPTW adjustment, treatment modalities were not significantly associated with CSS in both Kaplan-Meier analysis(p=0.065) and univariate Cox regression(p=0.068). After weighting, Kaplan-Meier analysis revealed a significant CSS difference favoring surgery (p=0.015), and univariate Cox regression showed surgery (p=0.018), race (p<0.001), tumor size (p=0.024) and radiotherapy (p=0.0003) as independent predictors. On subgroup analysis of patients receiving single-modality therapy, landmark analysis beyond 60 months showed improved CSS with surgery versus radiotherapy (p<0.001) after IPTW adjustment. Additionally, Kaplan-Meier analysis showed no pre-IPTW (p=0.68) or post-IPTW (p=0.30) CSS differences between surgery alone and surgery plus radiotherapy. Conclusion This population-based analysis demonstrated a potential survival advantage of surgery over radiotherapy for non-nasopharyngeal head and neck LEC after accounting for confounding factors. Additional comparative effectiveness data, ideally from controlled studies, are warranted to further investigate optimal treatment strategies.